Fate of Transforming Deoxyribonucleic Acid After Uptake by Competent Bacillus subtilis: Phenotypic Characterization of Radiation-Sensitive Recombination-Deficient Mutants - Dubnau, D. (1973)
A collection of 16 isogenic recombination-deficient strains of Bacillus subtilis isolated on the basis of sensitivity to methyl methane sulfonate (MMS) or mitomycin C (MC) were characterized phenotypically. All were found to be somewhat sensitive to ultraviolet irradiation, MC, and MMS. The mutants were all blocked in “late” steps in the transformation process and were provisionally grouped into four categories on the basis of the various properties examined. Class I mutants were deficient in transformation and heterologous transduction with phage PBS1 but were transducible with homologous donors at nearly the wild-type frequency. They were blocked in donor-recipient complex (DRC) formation but formed essentially normal amounts of double-strand fragments (DSF) and single-strand fragments (SSF). The class IIa strain was deficient in transformation and PBS1 transduction, and formed DRC which was normal by all available physical and biological criteria. Class IIb mutants were deficient in transformation and PBS1 transduction, and failed to form DRC. They did produce DSF and SSF. Class III mutants were deficient in transformation, were normal in PBS1 transduction, and formed DRC which was physically indistinguishable from that of the Rec(+) parent although with slightly lowered donor-type transforming activity. Class IV strains were deficient in PBS1 transduction but were transformed at nearly the wild-type efficiency. None of the mutant strains was deficient in the adenosine triphosphate-dependent deoxyribonuclease.